Rozwiązane

NA TERAZ SZYBKO PLIS​



NA TERAZ SZYBKO PLIS class=

Odpowiedź :

Odpowiedź:

zad 3

S = (a + 2t)/3

3S = a + 2t

2t = 3S - a

t = (3S - a)/2

P = t - 3rt + 2

3rt = t - P + 2

r = (t - P + 2)/3t

F = (4y - z)/3

3F = 4y - z

z = 4y - 3F

Odpowiedź:

Szczegółowe wyjaśnienie:

S= (a+2t)/3   *3

3S=a+2t

3S-a=2t  * :2

t= (3S-a)/2

P=t - 3rt + 2

P= t(1-3r)+2  

P-2=t(1-3r)       :t

(P-2)/t = 1-3r

(P-2)/t -1 = -3r    :(-3)

(P-2)/(-3t) + 1/3 = r

F= (4y-z)/3    *3

3F= 4y-z

z=4y-3f